Modification of the program «Young tourists-local historians» as a means of meeting the educational needs of schoolchildren with intellectual disorders - Syniov , Viktor; Kovalenko , Viktoriia (Scientific notes of the pedagogical department, 2022)
The article considers the problem of modification of the curriculum «Young tourists-local historians» of the tourist-local history direction of out-of-school education of primary level for primary schoolchildren with intellectual disabilities. The aim of the article is to reveal the content of the modification of the program «Young tourists-local historians» as a means of meeting the educational needs of students with intellectual disabilities. Modification is seen as a strategy to simplify the content of the curriculum, teaching and, as a result, the level of knowledge and skills that a child must acquire during learning. The theoretical basis for the modification of the curriculum was the conditions of quality education of children with intellectual disabilities, defined by V. M. Sinyov. Modification of the program was carried out taking into account the modal-specific patterns of physical, intellectual development and the level of socialization of primary school students with intellectual disabilities. The purpose of the training program «Young tourists-local historians» is to promote the development and socialization of children with intellectual disabilities by involving them in tourism, sports and local history activities and the formation of educational, cognitive, life-practical, civic and social; environmental and health competencies. Structural and substantive sections of the modified curriculum are: general propaedeutic; tourist and sports training; local lore; physical culture and safety of life. The content of these sections is studied by children for four years. The content of the program takes into account the requirements of the State standard of basic and complete general secondary education in the fields of «Social Sciences», «Health and Physical Culture», «Natural Sciences». The program contains information that deepens and complements the content of disciplines studied in general secondary education, including special schools, such as: «Science», «Fundamentals of Health», «I am in the world» and correctional and developmental program «Social and household orientation». The presented program was implemented in the activities of the Municipal Institution «Kharkiv Regional Station of Young Tourists» of the Kharkiv Regional Council, Volyn Center for National and Patriotic Education, Tourism and Local History and its effectiveness was proved.